Global and regional alterations of hippocampal anatomy in long‐term meditation practitioners. Issue 12 (19th July 2012) - Luders, Eileen; Thompson, Paul M.; Kurth, Florian; Hong, Jui‐Yang; Phillips, Owen R.; Wang, Yalin; Gutman, Boris A.; Chou, Yi‐Yu; Narr, Katherine L.; Toga, Arthur W.
<x xml:space="preserve">Abstract</x> Studies linking meditation and brain structure are still relatively sparse, but the hippocampus is consistently implicated as one of the structures altered in meditation practitioners. To explore hippocampal features in the framework of meditation, we analyzed high‐resolution structural magnetic resonance imaging data from 30 long‐term meditators and 30 controls, closely matched for sex, age, and handedness. Hippocampal formations were manually traced following established protocols. In addition to calculating left and right hippocampal volumes (global measures), regional variations in surface morphology were determined by measuring radial distances from the hippocampal core to spatially matched surface points (local measures). Left and right hippocampal volumes were larger in meditators than in controls, significantly so for the left hippocampus. The presence and direction of this global effect was confirmed locally by mapping the exact spatial locations of the group differences. Altogether, radial distances were larger in meditators compared to controls, with up to 15% difference. These local effects were observed in several hippocampal regions in the left and right hemisphere though achieved significance primarily in the left hippocampal head. Larger hippocampal dimensions in long‐term meditators may constitute part of the underlying neurological substrate for cognitive skills, mental capacities, and/or personal traits associated with the practice of meditation. Alternatively, given that meditation positively affects autonomic regulation and immune activity, altered hippocampal dimensions may be one result of meditation‐induced stress reduction. However, given the cross‐sectional design, the lack of individual stress measures, and the limited resolution of brain data, the exact underlying neuronal mechanisms remain to be established. Hum Brain Mapp 34:3369–3375, 2013. © 2012 Wiley Periodicals, Inc.